Localised protests, acquiescent villagers and local state brokers: managing pollution in a Chinese village. Learning to live with pollution: how Chinese villagers redefine their interests - Lora-Wainwright, A; Wu, Y; Zhang, Y; Van Rooij, B (2011)
It is often assumed that when citizens do not oppose pollution, it is due to their ignorance of its effects or to structural barriers to change. Based on participant observation and semi-structured interviews in a heavily industrialised village in South-West China, this paper argues that a sense of inevitability of pollution is just as important an obstacle. We argue that perceptions of inevitability were produced by (1) interdependence between villagers, village leaders, and industries; (2) experiences with protests; and (3) an understanding of locality within the wider national project of development. By examining a few key instances of collective action against Linchang, a very large and partly state-owned fertiliser plant, we trace how locals‟ strategies of action and their demands adapted in view of their experiences. Conversely, we show that village officials‟ attitudes to collective action and their role in channelling local discontent and obtaining redress has shifted over time. In doing so, we provide a model for understanding the gradual processes whereby environmental subjects are formed. Our observations on the localisation of protests problematise any simplistic understanding of these protests as “resistance”.